NAVIGATING NEW BEGINNINGS: ETHICAL AND LEGAL CONSIDERATIONS OF EGG FREEZING FOR MUSLIM WOMEN - Mutmainnah, Iin; Hasim, Hasanuddin (Jurnal Al-Dustur, 2024)
Egg freezing also known as Oocyte Cryopreservation, is a scientific advancement in the field of medicine that has a significant influence on society. Women undergo egg freezing as a proactive measure to preserve their fertility for future use when their reproductive capabilities decline. The objective of this research is to address the legality of egg freezing performed by women prior to marriage and its influence on the legal status of the children born as a result of the procedure in a review of Islamic law. The library research method is employed in this study, which pertains to the legal standards included in the principles of Islamic law alongside related laws and regulations. Data collection techniques involve the acquisition of relevant papers, journals, and publications. The research findings indicate that, according to the Egyptian fatwa and supported by the fatwa of the Indonesian Ulama Council (MUI), egg freezing is allowed under specific conditions. These conditions include ensuring that frozen egg cells are only fertilized with sperm cells from legally married couples, thereby enabling the production of lawful children in accordance with the law. However, if one were to contravene the conditions outlined in the fatwa, it would be considered forbidden and would lead to the ensuing kid being deemed illegitimate, hence being excluded from their father's lineage and inheritance entitlements.